2021
DOI: 10.1159/000518492
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Improves Liver Function in Rats by Upregulating Asparagine Synthetase

Abstract: <b><i>Introduction:</i></b> Canagliflozin (CANA) is a sodium-glucose cotransporter 2 inhibitor that was recently approved for treating diabetes. However, its effects on liver function are not well understood. The function of asparagine synthetase (ASNS) has been studied in several cancers but not in liver injury. Therefore, we investigated the connection between CANA and ASNS in alleviating damage (i.e., their hepatoprotective effect) in a rat liver injury model. <b><i>Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Based on current evidences, we conclude that Cana may regulate ferroptosis to modify DCM by balancing cardiac iron homeostasis and overexpressing xCT (Figure 6). Further, it has been reported that Cana can activate AMPK/Nrf2/ATF4 pathway and inhibit p53 expression (44,45). Nuclear factor erythroid 2-related factor 2 (Nrf2) and activating transcription factor 4 (ATF4) activated xCT expression by interacting with its promoter, while the deubiquitination of histone H2B by p53 inhibited xCT expression (46).…”
Section: Discussionmentioning
confidence: 99%
“…Based on current evidences, we conclude that Cana may regulate ferroptosis to modify DCM by balancing cardiac iron homeostasis and overexpressing xCT (Figure 6). Further, it has been reported that Cana can activate AMPK/Nrf2/ATF4 pathway and inhibit p53 expression (44,45). Nuclear factor erythroid 2-related factor 2 (Nrf2) and activating transcription factor 4 (ATF4) activated xCT expression by interacting with its promoter, while the deubiquitination of histone H2B by p53 inhibited xCT expression (46).…”
Section: Discussionmentioning
confidence: 99%
“…Several SGLTi drugs, including sotagliflozin, have gained major regulatory agencies' approval for treating diabetes. Some of these have shown unexpected beneficial effects on cardiovascular and renal disease risks (22)(23)(24), and on non-CF liver diseases (38)(39)(40)(41)(42). As shown in Figure 4, A-C, SGLT1 was upregulated in the CF rabbit livers.…”
Section: Resultsmentioning
confidence: 93%